2019
DOI: 10.1007/s11432-019-1470-x
|View full text |Cite
|
Sign up to set email alerts
|

Unscented Kalman-filter-based sliding mode control for an underwater gliding snake-like robot

Abstract: With its strong endurance and high maneuverability, an underwater gliding snake-like robot (UGSR) is a strong potential candidate for aquatic exploration and monitoring. The major feature of the UGSR, which distinguishes it from other snake-like robots, is long range and long operation duration by gliding. This study establishes a gliding motion control system for the UGSR based on a sliding mode controller (SMC). The control system stabilizes the system and suppresses the uncertainties and unknown disturbance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…To obtain the motion information and guidance law, the measured data need to be processed by the Kalman filter. For data link information, the linear Kalman filter (KF) is selected, while for missile angle information, we choose the Unscented Kalman filter (UKF) [10].…”
Section: Problem Descriptionmentioning
confidence: 99%
“…To obtain the motion information and guidance law, the measured data need to be processed by the Kalman filter. For data link information, the linear Kalman filter (KF) is selected, while for missile angle information, we choose the Unscented Kalman filter (UKF) [10].…”
Section: Problem Descriptionmentioning
confidence: 99%
“…But not much concentration was given to noise and matched disturbances. Later in 2020, Tang et al (2020) suggested an unscented Kalman filter (UKF) with SMC to enhance the robustness and tracking even in the presence of noise parameters for the underwater gliding snake-like robot. Thus, it can be seen that most of the works in SMC and K for disturbance observer were applied to mostly electrical processes.…”
Section: Introductionmentioning
confidence: 99%